Simulating and Analyzing the Behavior of Table-Driven and On-Demand Routing Protocol - Atri, Swati; Tyagi, Sanjay (International Journal of Computer Sciences and Engineering, 2025)
Routing is a mechanism to find an optimal route from a source node to destination which is the responsibility of routing protocols. Two prominent routing protocols are reactive or on-demand routing protocols and proactive or table-driven routing protocols. Both types of protocols are efficient in themselves. Performance evaluation of protocols by using performance metrics such as PDR, Average End to End delay, Routing Overhead and throughput etc. is an important aspect in estimating the efficiency of protocols. It helps in making choice of protocols according to the network environment and conditions. This paper describes routing behavior of on-demand routing protocols (DSR, AODV) and table-driven routing protocol (DSDV). Simulations of these three protocols have been performed on NS-2 by varying pause time and speed and then results have been analyzed.